Experimental research models for skeletal muscle contraction - Yasuko Manabe; Nobuharu L. Fujii (Japanese Society of Physical Fitness and Sports Medicine, 2016)
Skeletal muscle has an important role besides its obvious function in physical movement and locomotion; namely, it maintains whole-body metabolism. Maintaining muscle mass and quality with regular exercise is closely related to quality of life and a healthy life expectancy. However, the ways that exercise, and muscle contraction, in particular, contribute to our health has not been analyzed in detail. Progressive elucidation of the intracellular mechanisms underlying the metabolic changes induced by exercise/contraction and the hormones secreted from skeletal muscle (called myokines) is providing new insights into how exercise affects our health. To research these mechanisms in muscle contraction, various in vivo and in vitro experimental models have been developed. This review article outlines the existing skeletal muscle contraction models in rodents. Each model has its advantages and disadvantages. It is important to keep such features in mind when selecting an appropriate contraction model for the particular experimental purpose.